Strategien und Lösungen bei der Übersetzung von identitätsstiftenden Unternehmenstexten am Beispiel einer Kundenzeitschrift - Błaszkowska, Hanka (2022)
The article addresses the phenomenon of corporate language and the transfer of its semantic-lexical means, such as company-specific technical terms, from German into Polish based on customer communication texts of one automotive company. The concept of corporate language has evolved from normative-practical concepts, such as corporate wording, to linguistically-based models, such as corporate style. A corporate language is a single-language phenomenon, however, in international corporate communication issues of corporate text translation play an important role, and attention must also be paid to the company-specific language style that sets the company apart from competitors in the same industry. A corporate language comes into play especially in the area of external communication. Therefore, this article exemplarily investigates texts in this field, specifically customer magazine texts. It also addresses the links between linguistic style and corporate identity, which must be given linguistic expression in the target texts.
Keywords: automotive industry; corporate identity; corporate communication; corporate language; corporate style; company-specific terms; customer magazine; translation from German into Polish